Characterization of the Effect of Increased Plant Density on Canopy Morphology and Stalk Lodging Risk - Sher, Alam; Khan, Aaqil; Ashraf, Umair; Liu, Hui Hui; Li, Jin Cai (Frontiers in Plant Science, 2018)
Plants react to the environment and to management interventions by adjusting architectural and structural modifications. A field trial was conducted in China during 2016 to study the plant population effects on maize canopy morphological development. The main objectives of the current study were (i) characterize the effects of increased plant density on canopy morphology and stalk lodging (ii) exploring the relationships between organ morphology and stalk lodging. The field experiment was composed of five plant densities (4.5, 6, 7.5, 9 and 15 plants m-2 with three cultivars Zhengdan 958 (lodging-resistant cultivar), Longping 206 and Jinqiu119 (lodging-susceptible cultivars). Laminae and sheaths lengths increased in lower phytomers but decreased in upper phytomers in response to plant densities for all cultivars. Lamina width and internode diameter decreased for all phytomers in response to plant densities for all cultivars. Correlation between organ morphology, plant density and stalk lodging was linear. Data obtained from characterization used in this study (i.e., canopy morphology, correlation of organ morphology with stalk lodging traits in response to various plant densities for different cultivars etc.) will be useful in future modeling studies to predict canopy morphological characteristics as affected as interplant competition and stalk lodging.